2017
DOI: 10.1016/j.genhosppsych.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Conversion disorder: A systematic review of current terminology

Abstract: Objective: It has been argued that the label given to unexplained neurological symptoms is an important contributor to their often poor acceptance, and there has been recent debate on proposals to change the name from Conversion Disorder. There have been multiple studies of layperson and clinician preference and this article aimed to review these.Design: Multiple databases were searched using terms including "conversion disorder" and "terminology", and relative preferences for the terms extracted.Results: Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Although this term is more acceptable to patients than the term pseudoseizures, 16,18 and popular among neurologists and epileptologists, 17,19 it is nonetheless a "negative" diagnostic term, which focuses on what the patient does not have, rather than giving the patient a positive explanation for their symptoms. Systematic reviews have shown that the most popular term among patients (and clinicians) for conversion disorder is "functional," 21 and studies that have assessed its use in patients specifically with seizure disorders corroborate these findings. 16 However, in this survey, only 28% of GPs used this term.…”
Section: Discussionmentioning
confidence: 98%
“…Although this term is more acceptable to patients than the term pseudoseizures, 16,18 and popular among neurologists and epileptologists, 17,19 it is nonetheless a "negative" diagnostic term, which focuses on what the patient does not have, rather than giving the patient a positive explanation for their symptoms. Systematic reviews have shown that the most popular term among patients (and clinicians) for conversion disorder is "functional," 21 and studies that have assessed its use in patients specifically with seizure disorders corroborate these findings. 16 However, in this survey, only 28% of GPs used this term.…”
Section: Discussionmentioning
confidence: 98%
“…The terminology for FNDs has evolved over the centuries, and includes the following: hysteria, psychogenic complaints, dissociative states, neurologically unexplained symptoms, somatoform, and conversion disorder. The currently favored term functional neurological disorder emphasizes how the condition is a disorder of function, not of structure or disease. Major risk factors for FNDs include psychosocial stressors and posttraumatic stress disorder (PTSD) …”
Section: Introductionmentioning
confidence: 99%
“…While "psychogenic," "psychosomatic," and "nonorganic" all remain in use, there is growing preference for the word "functional". 9 Within the field of neurology, the term FND is more commonly used than FNSD or conversion disorder, and additional diagnostic labeling is often used to distinguish among different presentations. For example, functional motor disturbances can be referred to as functional movement disorders and can be further subdivided into functional gait disturbance, tremor, dystonia, myoclonus, chorea, and weakness.…”
Section: Overvie W Of Fun C Tional Neurolog Ic Al Disorder Smentioning
confidence: 99%
“…In contrast to the specific language of the DSM‐5, the informal labels given to medically unexplained symptoms remain somewhat heterogeneous. While “psychogenic,” “psychosomatic,” and “nonorganic” all remain in use, there is growing preference for the word “functional” 9 . Within the field of neurology, the term FND is more commonly used than FNSD or conversion disorder, and additional diagnostic labeling is often used to distinguish among different presentations.…”
Section: Overview Of Functional Neurological Disordersmentioning
confidence: 99%
See 1 more Smart Citation